2017
DOI: 10.6026/97320630013261
|View full text |Cite
|
Sign up to set email alerts
|

Druggability and Binding Site Interaction Studies of Potential Metabolites Isolated from Marine Sponge Aurora globostellata against Human Epidermal Growth Factor Receptor-2

Abstract: To study the involvement of compounds stigmasterol and oleic acid isolated from marine sponge Aurora globostellata and docking against the Human Epidermal Growth Factor Receptor-2 in breast cancer. The comparative molecular docking was performed with the natural compounds from marine sponge and the synthetic drugs used in breast cancer treatment against the target HER2. The molecular docking analysis was done using GLIDE in Schrodinger software package. The ADME properties were calculated using the Qikprop. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Addition of hydrogen atoms to the protein was performed using CHARMm force field. Energy minimization was performed by using conjugate gradient method with an RMS gradient of 0.01kcal/Å mol on Argus lab [10, 11,12].…”
Section: Molecular Docking Of Hbv Dna Polymerase With Chalconesmentioning
confidence: 99%
See 2 more Smart Citations
“…Addition of hydrogen atoms to the protein was performed using CHARMm force field. Energy minimization was performed by using conjugate gradient method with an RMS gradient of 0.01kcal/Å mol on Argus lab [10, 11,12].…”
Section: Molecular Docking Of Hbv Dna Polymerase With Chalconesmentioning
confidence: 99%
“…The results of the docking enabled the ranking of the docked conformation of the ligands according to their docking score and hydrogen-binding site. Based on standard antiviral drug, chalcones compound were selected as hits for the target protein [10, 11,12].…”
Section: Molecular Docking Of Hbv Dna Polymerase With Chalconesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other word, the fraction containing the stigmasterol can only affect cancer cells. Previous studies conducted on stigmasterol extracted from the Aurora globostellata sponge, showed the inhibitory effect on the growth of breast cancer cells (Sugappriya et al, 2017), and observed that, the stigmasterol and its derivatives extracted from Xestospongia sp marine sponge can result in killing 50% of the lymphocyte cancer cells (K562) at 18/3 to 34/3 μg/ml (Cheng et al, 2016). In another study conducted on the cytotoxic properties of the extract containing stigmasterol (more than 25%) from the Spanish and Portuguese marine sponges on the LLC-MK2 healthy cells (epithelial cells from the kidney of the monkey Macaca mulatta), it has been shown that, Tethya ignis (177.5 μg/ml), Tethya rubra (172.5 μg/ml), Dysidea avar (144.2 μg/ml), and Mycale angulosa sponges (302.71 μg/ml) can exhibit lethal effects (Paula et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies have reported the cytotoxic activity of isolated compounds against different human cancer cell lines, viz., stigmasta-5, 22-dien-3-ol, octadecenamide, and umbelliferone through various mechanisms and pathways. The anticancer activity of stigmasterol against Ehrlich ascites carcinoma [21], breast cancer cells [30], liver cancer cells [31], and Hela cells [32] were reported in the literature. The anticancer activity of umbelliferone against HepG2 hepatocellular carcinoma cells via the induction of apoptosis and cell cycle [33] and human renal cell carcinoma [34] were reported.…”
Section: Discussionmentioning
confidence: 99%